(untitled) (World Economics and Finance Bulletin, 2023)
The article discusses ways for examining an enterprise’s financial state as a factor that represents the most significant aspects of the enterprise, such as its capacity for doing business, the degree of economic interests of the enterprise, and its competitiveness. A rapid response to changes in the organization’s influencing factors enables you to adapt the economic component in line with market demands